2008
DOI: 10.1007/s10461-008-9481-2
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Follow-Up of Sexual Behavior Among HIV-Uninfected Household Members of Adults Taking Antiretroviral Therapy in Uganda: No Evidence of Disinhibition

Abstract: This paper examines HIV risk behavior among HIV-uninfected adults living with people taking antiretroviral therapy (ART) in Uganda. A prospective cohort of 455 HIV-uninfected non-spousal household members of ART patients receiving home-based AIDS care was enrolled. Sexual behavior, HIV risk perceptions, AIDS-related anxiety, and the perception that AIDS is curable were assessed at baseline, 6, 12 and 24 months. Generalized linear mixture models were used to model risk behavior over time and to identify behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 29 publications
5
35
1
Order By: Relevance
“…This may have limited the strength of our conclusions; however, our laboratory-confirmed findings of only one sero-conversion in 3 years among 62 sero-discordant couples were consistent with the estimated risks. Lastly, this analysis did not include assessment of potential risk compensation in other household or community members, and thus could underestimate disinhibition effects, although an earlier analysis of the household member' sexual behavior showed no indications of disinhibition [26].…”
Section: Discussionmentioning
confidence: 99%
“…This may have limited the strength of our conclusions; however, our laboratory-confirmed findings of only one sero-conversion in 3 years among 62 sero-discordant couples were consistent with the estimated risks. Lastly, this analysis did not include assessment of potential risk compensation in other household or community members, and thus could underestimate disinhibition effects, although an earlier analysis of the household member' sexual behavior showed no indications of disinhibition [26].…”
Section: Discussionmentioning
confidence: 99%
“…A population-based survey in Kenya suggested that individuals who reported higher risk compensation (that is increased sexual risk taking now that ARTwas available) and a belief that ART cures HIV were more likely to be infected with HIV [63], perhaps suggesting therapeutic optimism. A study conducted among HIV-uninfected nonspousal household members of adults taking ART in Uganda found that perceiving HIV as curable and lower AIDS-related anxiety were independently associated with risky sex [64]. Despite expanding access to ART and HIV prevention services in hyperendemic settings, uptake of HIV testing remains relatively low and a substantial proportion of at-risk individuals continue to engage in unprotected sex [65,66].…”
Section: Ecological Studiesmentioning
confidence: 99%
“…25 28ā€“30 The recruitment setting was community-based (n=5),19 22 24 28 30 clinic-based (n=3),20 21 27 a combination of community-based and clinic-based (n=5)23 25 26 29 31 and workplace-based in one study 32. The majority of studies were prospective cohorts (n=9),20 21 23 24 26ā€“28 31 32 while the remainder were randomised controlled trials (n=5) 1922 25 29 30…”
Section: Resultsmentioning
confidence: 99%
“…23ā€“25 27 31 32 Participants in all 14 studies underwent either individual19 20 22 24 26ā€“32 or couples21 counselling, or a combination of both 2325 Of studies specifying whether counselling was pre-testing or post-testing, two used post-test counselling only,20 32 while two used both 25…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation